Effective Dispersion of Carbon Nanotube in Epoxy Grout for Structural Rehabilitation - Lim, Kar Sing; Seng, Hai Kam; Zardasti, Libriati; Nordin, Yahaya; Norhazilan, Md Noor (EDP Sciences, 2018)
The industry nowadays is incorporating the composite repair system for repairing pipelines rather than the conventional steel repair. The mechanism of this repair method usually consists of three components which are the composite wrapping, infill material and the adhesive. However, there has been very little research on the function of the infill in the repair mechanism. This work is concerning the enhancement of the performance or the strength properties of the infill material in pipeline repair by reinforcing the putty with carbon nanotubes (CNT). The enhancement of the performance of the infill has been carried out by dispersing the CNT into epoxy resin with a three roll mill. In the mechanical properties testing, it is found that the CNT is an effective material to improve the tensile strength of the epoxy grout. However, the CNT-modified samples in the compressive property test show a contrast to the tensile test. All the CNT-modified samples exhibit a lower compressive strength than the control sample and the milled down sample. In conclusion, CNT shows the potential to be a very good material to enhance the mechanical properties of epoxy grout, however, with this specific brand of epoxy grout that contains steel filler in the resin, the CNT only improve the tensile properties but the compressive properties of the epoxy grout has been compromised as compared to the control sample.